Cyber Security and Digital Transformation in Strategic Management Accounting: A Systematic Literature Review of Their Roles in Achieving Competitive Advantage - Mohammad Chaidir; Moh Zalmi Kahardian (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
This study presents a qualitative Systematic Literature Review (SLR) examining the roles of Cyber Security (CS) and Digital Transformation (DT) in strengthening Strategic Management Accounting (SMA) to achieve sustainable Competitive Advantage (CA). Following the PRISMA 2020 framework, peer-reviewed studies published between 2015 and 2025 were systematically identified, screened, and synthesized from major academic databases. The findings indicate that SMA has evolved into a strategic capability supporting data-driven decision-making, while DT enhances organizational agility, innovation, and analytical capabilities through advanced digital technologies. Simultaneously, CS safeguards digital assets, ensures information integrity, strengthens organizational resilience, and supports business continuity. The review demonstrates that integrating SMA, DT, and CS creates complementary strategic capabilities that significantly improve organizational performance and long-term competitiveness. The study contributes to the literature by providing an integrated conceptual framework and identifying future research opportunities concerning digital accounting, cybersecurity governance, and sustainable competitive advantage in the digital economy.